1977
DOI: 10.1210/jcem-45-5-1124
|View full text |Cite
|
Sign up to set email alerts
|

Glucose, Insulin and Somatostatin Infusion for the Determination of Insulin Sensitivity

Abstract: Glucose, insulin and somatostatin infusion over 2 hours effectively suppressed endogenous secretion of insulin, glucagon and growth hormones. Steady state plasma glucose level (SSPG) which should be inversely proportional to insulin sensitivity was obtained. In 6 adult-onset non-obese untreated diabetics, mean value of insulin sensitivity indices was significantly reduced compared with normal. In 5 insulin-treated diabetics and in 5 subjects with borderline glucose tolerance including 2 obese subjects, insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(73 citation statements)
references
References 0 publications
4
67
0
2
Order By: Relevance
“…A study [13] showed that the concentrations of soluble ICAM-1, VCAM-1, and E-selectin correlate with the degree of insulin resistance calculated from a modified insulin suppression test [25] in healthy volunteers. We did not find a correlation between the extent of insulin resistance, determined by the euglycaemic hyperinsulinaemic clamp and the concentration of plasma ICAM-1 or VCAM-1 in any group.…”
Section: Discussionmentioning
confidence: 99%
“…A study [13] showed that the concentrations of soluble ICAM-1, VCAM-1, and E-selectin correlate with the degree of insulin resistance calculated from a modified insulin suppression test [25] in healthy volunteers. We did not find a correlation between the extent of insulin resistance, determined by the euglycaemic hyperinsulinaemic clamp and the concentration of plasma ICAM-1 or VCAM-1 in any group.…”
Section: Discussionmentioning
confidence: 99%
“…A modified insulin suppression test [17,18] was carried out on all the subjects at the end of the dietary period. The study began at 8:00 am, after 12 h of fasting.…”
Section: Glucose Suppression Testmentioning
confidence: 99%
“…The high levels of 24-hr UCPR in NIDDM-NO were thought to be induced by uncontrolled plasma glucose levels. Harano et al (1977) reported that reduced insulin sensitivity could not be improved with dietary therapy in his evaluating system using cyclic somatostatin to suppress the endogenous secretions of insulin, glucagon and growth hormone in adult-onset, non-obese, untreated diabetics. In the present study, ISI in NIDDM-NO, obtained according to the method of Harano et al (1977), were significantly lower than those in healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The insulin sensitivity test was made according to the method of Harano et al (1977). The procedure was as follows (Fig.…”
Section: Methodsmentioning
confidence: 99%